Effect of Finnsheep crossbreeding on Lamon sheep performance: in vivo traits - Bittante, G.; Pastore, E. (Agricultural and Food Science, 1988)
The objective of this trial was the comparison of the in vivo traits of Lamon (L), a local meat breed of the Eastern Italia Alps, and Finnsheep X Lamon (F x L) fattening lambs. Forty-one lambs (25 L and 16 F x L) of both sexes were weaned at 8 weeks of age and fattened for 14 weeks. The diet (11,6 MJ/kg d.m.M.E.) consisted of maize silage ad lib., 200 g/d of dried sugar beet pulp, 150 g/d of soybean meal and 30 g/d supplement. F x L lambs grew slightly more than L lambs (197 vs 176 g/d; P < .1) during the suckling period but not during the fattening period (207 vs 203 g/d; n.s.), reaching a slightly higher slaughter weight (36.9 vs 35.5 kg; n.s.). Crossbred lambs consumed, during fattening, slightly more d.m. (75.9 vs 73.1 g • d-1 • kg-1 • L.W.-75) and M.E. ( .88 vs .85 MJ • d-1 • kg-1• L.W.-75). D.M. conversion was not different (4.24 vs 4.16; P > .1) while M.E. requirements for growth, estimated assuming a maintenance requirement of.44 MJ • d-1 • kg-1 • L.W.-75, resulted higher (+7 %) for F x L than for L lambs (2.18 vs 2.04 MJ • kgDG • kg-1 • L.W.-75; P < .1). The ram-lambs showed superior growth potential and feed efficiency in respect to the ewe-lambs. In conclusion it appears that crossbreeding with Finnsheep is not detrimental to the in vivo performance of fattening Lamon lambs except for a slight increase of the energy requirements for growth.